The Newfoundland Woods Labour Board - Gushue, R. (Relations industrielles / Industrial Relations, 1956)
SummaryIn this article, the author intends to give to the reader a good idea of the Newfoundland Woods Labour Board. After a short description of the situation leading to its formation, he exposes its organization, development and continuance under several chairman; he also presents an interesting composition of the woods labour rates and working conditions in 1940 and 1955 and some activities and accomplishments of the Board. Finally, his analysis of the results of the Board's operations proves that labour and management can effectively co-operate.